A Solar-Powered Automated Irrigation System Using Arduino and Moisture Sensors for Efficient Water Management in Agriculture - Chan, Choon Kit; Malwe, Prateek D.; Mandlik, Vinayak T.; Jaiswal, Naresh; Jadhav, Shivaji B.; Sapkal, Narayan; Bhopale, Narendra; Sonawane, Chandrakant R.; Singh, Subhav; Varshaney, Deekshant; Kumar, Satish (Engineering, Technology & Applied Science Research, 2025)
As agriculture is the primary source of food in many countries, effective irrigation systems are crucial. This article presents a system that can regulate irrigation based on demand using Arduino Uno, a solar-powered water pump, and an autonomous water flow control system with a moisture sensor to reduce water consumption and time. Traditional irrigation methods often lead to inefficient water use due to a lack of real-time monitoring and control, especially in regions with limited water resources. In addition, manual irrigation systems are time-consuming and can result in over- or under-irrigation, affecting crop yield and resource management. With increasing concerns about water scarcity and the need for sustainable agriculture, there is a critical need for automated irrigation solutions that are both energy-efficient and cost-effective. The proposed system aims to optimize water usage based on soil conditions in real time. This system can be applied to farms, parks, and other locations that require efficient irrigation systems. The proposed approach supports aggressive water management for agricultural land, reduces power costs, is cheap, has a small size, and is highly adaptable. This system is especially beneficial for farmers and gardeners who may not have the time or resources for regular irrigation. Assessing real-time soil moisture levels can ensure that crops receive optimal water supply based on actual needs.